KAJIAN UMUM TENTANG AUTOPSI VERBAL - Eriliana Aryanti; Dhian Kartikasari; Tommy Kristanto (Faculty of Medicine, Universitas Islam Indonesia, 2020)
An sudden death is a case that occurs without prior health complaints, so that its cause cannot be identified. On a death certificate, a doctor needs to state a cause of death, so an autopsy is usually required to confirm the cause of the sudden death. Implementation of autopsies in cases of sudden deaths at the forensic medicine installation of Dr. Soetomo Hospital during 2014-2016 periods was only around 12%. This research is a literature review. A verbal autopsy is suggested to be useful to determine a valid cause of a death; therefore, recording of deaths in the hospital will be more accurate. WHO has published various standards of verbal autopsies in 2012. Validation of the verbal autopsies by questionnaires has shown an acceptable diagnostic accuracy to identify a cause of death compared to a cause of death obtained from medical records.